Social communication networks and videoconferencing - Ian Saunderson; Gideon de Wet (Communicare)
This study examined new organisational environments and environmental variables involved in the adoption and implementation of new communication technology. This includes structures within the organisation and social communication networks. Social communication networks determine the levels of the measurement of the processes associated with managerial practices and policies regarding videoconferencing implementation. Videoconferencing as a communication management tool should not only take into account the numerous applications of videoconferencing, but also consider all the implications for management. The study utilised focus group research, social network analysis and descriptive statistics in the investigation of the manifestation of the above-mentioned variables in the Tertiary Education Linkages Project (TELP), which is a linkage project between the Eastern Cape Technikon and Texas Southern University. The study utilises triangulation for the establishment of acceptable levels of reliability and validity. The data analysis revealed that videoconferencing facilitates organisational communication networks on the precondition that communication networks and the communication environment are well managed. The nature of social networks reveals that it will always be in existence where human interaction is present. However, communication management strategies are indeed required to ensure that the quality of information disseminated over the social network contributes to sound managerial outcomes. It was furthermore established that communication management policies do not necessarily affect individuals’ experiences of videoconferencing. However, as a communication management tool, videoconferencing must be guided by effective communication management policies and practices for the group to be effective.